Reconciling Tradition and Modernity: A Critical Review of Sexuality Education in the Indonesian Pesantren Context - Mainuddin; Syamsul Arifin; M. Nurul Humaidi; Romelah (Lembaga Bale Literasi, 2025)
This article examines how sexuality education in Indonesian pesantren can reconcile Islamic tradition with contemporary reproductive health concerns. Although sexuality-related material has long existed in pesantren through classical fiqh and yellow-book instruction, it has largely been limited to legal-formal themes such as taharah, puberty, menstruation, aurat, and marital ethics, with little attention to consent, bodily boundaries, reproductive health literacy, and sexual violence prevention. Using a qualitative critical literature review, this study analyzes Islamic texts and scholarly publications published between 2015 and 2025, retrieved through Scopus and Google Scholar using the keywords sex education, pesantren, Islamic tradition, and modernity. Data were interpreted through content analysis and critical discourse analysis to identify possible intersections between maslahah-based Islamic reasoning and contemporary health-oriented perspectives. The findings show that the main challenge is not the absence of religious material, but the lack of epistemic reconstruction linking classical concepts to adolescents’ lived realities. Three major pathways emerged: expanding sexuality education beyond marital issues, integrating sexual violence prevention and bodily protection into the curriculum, and enriching traditional pedagogy with dialogical and participatory approaches. The study also finds that implementation requires collaboration among kyai, teachers, students, parents, communities, and the state to address sociocultural taboos and institutional limitations. This article argues that pesantren should be viewed not as barriers to sexuality education, but as institutions with internal theological and pedagogical resources for contextual renewal. It offers a conceptual framework for culturally grounded and religiously legitimate sexuality education in pesantren. Framework highlights the possibility of reconciling tradition and modernity.